2020
DOI: 10.1038/s43246-020-00078-y
|View full text |Cite
|
Sign up to set email alerts
|

Nacre toughening due to cooperative plastic deformation of stacks of co-oriented aragonite platelets

Abstract: Nacre’s structure-property relationships have been a source of inspiration for designing advanced functional materials with both high strength and toughness. These outstanding mechanical properties have been mostly attributed to the interplay between aragonite platelets and organic matrices in the typical brick-and-mortar structure. Here, we show that crystallographically co-oriented stacks of aragonite platelets, in both columnar and sheet nacre, define another hierarchical level that contributes to the tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…During formation, not-yet–calcified layers grow within multiple closely spaced sheaths that separate progressively during mineral growth ( 16 , 17 ). While some work has focused on describing the atomic-to-nanoscale structure of the tablets themselves as assemblies of nanoparticles of aragonite ( 18 21 ) or the atomic order within and between tablets ( 22 ), the current work is focused on how these tablets are arranged at the next length scale (hundreds of nanometers—several microns [i.e., herein, the mesoscale]).…”
mentioning
confidence: 99%
“…During formation, not-yet–calcified layers grow within multiple closely spaced sheaths that separate progressively during mineral growth ( 16 , 17 ). While some work has focused on describing the atomic-to-nanoscale structure of the tablets themselves as assemblies of nanoparticles of aragonite ( 18 21 ) or the atomic order within and between tablets ( 22 ), the current work is focused on how these tablets are arranged at the next length scale (hundreds of nanometers—several microns [i.e., herein, the mesoscale]).…”
mentioning
confidence: 99%
“…Recent studies on nacre showed that nanogranular biominerals exhibit coherent and continuous stress contours in their mesoscale building units across nacre tablets. 99 Nano-indentation experiments on nacre, followed in situ by high-resolution transmission electron microscopy, revealed those microstructural elements to interlock when loaded. Thus, strain contours can propagate across the microstructural elements in a relatively unhindered manner.…”
Section: Papermentioning
confidence: 99%
“…Thus, strain contours can propagate across the microstructural elements in a relatively unhindered manner. 90 Both experimental studies exemplified that mesoscale units cooperatively act when spreading the stress field, 90,99 which allowed us to focus our simulations on the wider stress field by employing simplified structural models.…”
Section: Papermentioning
confidence: 99%
“…Besides using fluorescence, stress can also be characterized using Raman spectroscopy in non-luminescent materials. This approach could be applied to other advanced ceramics like zirconia, or natural ceramics like apatite and calcium carbonates (Loh et al, 2020;Perrichon et al, 2017;Pezzotti and Sakakura, 2003;Pezzotti et al, 2012;Wei et al, 2020;Zhu and Pezzotti, 2011).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%